Analysis of Learning Strategies of Students with Intellectual Disabilities Using E-LAPD-Based Liveworksheets in Chemical Compound Nomenclature - Mochammad Rizky Kurniawan; Teguh Santoso; Rahmania Fitrah Sari; Muchlis; Dian Novita (Postgraduate, University of Mataram, 2025)
This study aims to analyze the learning strategies of students with intellectual disabilities using E-LAPD-based Liveworksheets on the nomenclature of chemical compounds by applying the UDL (Universal Design for Learning) approach. The research method used is a mixed of quantitative and qualitative. Quantitative analysis uses validation results and pretest and posttest scores. Pretest and posttest data were analyzed using N-gain. Qualitative analysis uses the results of interviews with students with intellectual disabilities, which will be analyzed using the NVivo application. The results of this study indicate that the application of the UDL (Universal Design for Learning) approach to students with intellectual disabilities is practical to implement. This is evidenced by the results of student interviews analyzed using the NVivo application using Cluster Analysis, grouping codes or themes based on their similarities in the text, producing a similarity matrix. In addition, this is evidenced by the pretest and posttest data analyzed using N-gain scores showing a good category with an N-gain score of ≥ 0.7. Based on these findings, it can be concluded that the application of the UDL (Universal Design for Learning) approach with E-LAPD to students with intellectual disabilities on the nomenclature of chemical compounds is practical to implement.